Awareness of disc herniation among general population in Aseer province, Saudi Arabia - Abdullah Khalid Alshehri (Journal of Family Medicine and Primary Care, 2019)
Background: Herniated lumbar disc is a depositions of discs material (nucleus pulposus and annulus fibrosus) behind the intervertebral disk. Intervertebral disc connected the vertebral bodies together by pad of fibrocartilage. The major functions of intervertebral disc are mechanical, transferring load coming from the body weight and muscle contractions by spinal columns and letting the curving, flexion, and contortion. Aim: To assess the awareness of general population in Aseer region, southern of Saudi Arabia, regarding disc herniation and to identify the predictors for their awareness. Methodology: A descriptive cross-sectional approach was conducted through a questionnaire designed to examine the public herniated disc awareness and knowledge. The questionnaire given to individuals from general population visiting general public places in Aseer region. Content validity for the questionnaire was done as it was reviewed by three experts for any modification of corrections. Results: The study included 1,044 participants aged between 15 and 70 years with mean age of 36.3 ± 11.2 years old. The majority of respondents were males (62.4%) and Saudi (98.9%). About 71% of the participants were university graduated. Generally, only 9% of the study participants recorded good awareness level regarding all aspects of disc herniation. Conclusion: This study showed that awareness regarding disc herniation among the general population was very poor for all domains.